Endothelial Dysfunction - Old Concepts and New Challenges 2018
DOI: 10.5772/intechopen.73025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advanced Glycation End Products on Endothelial Function and Their Potential Link to Atherosclerosis

Abstract: The role of advanced glycation end products (AGEs) in cardiovascular diseases is a matter of interest in the last years and the strong association between the action of AGEs on their receptor (RAGE) and atherosclerosis has attracted increased attention. The aim of this chapter is to review the results of our laboratory and others on the molecular mechanisms triggered by AGEs in the endothelium that could participate in the atherosclerotic process. These mechanisms and molecular pathways could be the source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Thus, the renin–angiotensin–aldosterone system may be upregulated in diabetes, resulting in increased blood pressure through a direct effect mediated by angiotensin II [ 106 ], as well as indirectly through upregulation of sympathetic activity [ 107 ]. Another essential connection between HTN and diabetes is the occurrence as well as the progression of diabetic kidney disease [ 108 ], the pathophysiology of which is mediated through several pathways including endothelial dysfunction and advanced glycation end-products [ 109 ]. Furthermore, obesity and metabolic syndrome, through their effects on various hormones and inflammation pathways, may also influence the occurrence of HTN and diabetes [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the renin–angiotensin–aldosterone system may be upregulated in diabetes, resulting in increased blood pressure through a direct effect mediated by angiotensin II [ 106 ], as well as indirectly through upregulation of sympathetic activity [ 107 ]. Another essential connection between HTN and diabetes is the occurrence as well as the progression of diabetic kidney disease [ 108 ], the pathophysiology of which is mediated through several pathways including endothelial dysfunction and advanced glycation end-products [ 109 ]. Furthermore, obesity and metabolic syndrome, through their effects on various hormones and inflammation pathways, may also influence the occurrence of HTN and diabetes [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 Experimentally, blockage of RAGE using soluble forms of RAGE or anti RAGE antibody decreased atherosclerotic lesion and VCAM-1 level. 31 In contrast, Alvarez et al 32 showed that blockage of RAGE was not sufficient to counteract the AGE-induced VCAM-1 expression, which may suggest that other RAGE independent mechanisms may be acting to increase adhesion molecule. As mentioned, neointimal proliferation is an essential process in AVF failure.…”
Section: Discussionmentioning
confidence: 95%
“…Their accumulation in CKD promotes endothelial dysfunction and subsequent diseases [ 115 , 116 , 117 , 118 , 119 , 120 ]. Atherosclerosis, autoimmune disease, diabetes mellitus, and inflammatory diseases are closely linked to the AGE receptor-ligand axis [ 121 , 122 , 123 , 124 ]. AGEs induce cell injury by interacting with their receptor, denominated receptor for advanced glycation end products (RAGE), which is a ubiquitous multiligand transmembrane cell surface receptor of the immunoglobulin superfamily [ 116 , 125 , 126 , 127 ].…”
Section: Transporters and Receptors Of Uremic Toxins In The Endothmentioning
confidence: 99%